2018
DOI: 10.1177/1524838018795269
|View full text |Cite
|
Sign up to set email alerts
|

Childhood Maltreatment and Violent Outcomes: A Systematic Review and Meta-Analysis of Prospective Studies

Abstract: The risk of violence following childhood maltreatment is uncertain. This meta-analytic review identified prospective studies that have examined this association. We systematically searched three electronic databases (PsycINFO, EMBASE, and MEDLINE) and completed a targeted search on Google Scholar. These were supplemented with scanning reference lists and correspondence with authors. We considered non-English-language and unpublished studies. Studies were included if childhood maltreatment was measured before a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
64
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 103 publications
(78 citation statements)
references
References 63 publications
9
64
1
Order By: Relevance
“…Third, there is a high co-occurrence of childhood sexual abuse with other forms of child abuse, which is associated with poorer psychosocial and health outcomes. [88][89][90] However, as a result of insufficient data, we were not able to take into account effects of other forms of child abuse in this umbrella review. Finally, our analyses showed that current evidence of the association between sexual abuse and health outcomes is inconsistent and studies with significant results were more likely to be published than those with non-significant findings.…”
Section: Fibromyalgiamentioning
confidence: 99%
“…Third, there is a high co-occurrence of childhood sexual abuse with other forms of child abuse, which is associated with poorer psychosocial and health outcomes. [88][89][90] However, as a result of insufficient data, we were not able to take into account effects of other forms of child abuse in this umbrella review. Finally, our analyses showed that current evidence of the association between sexual abuse and health outcomes is inconsistent and studies with significant results were more likely to be published than those with non-significant findings.…”
Section: Fibromyalgiamentioning
confidence: 99%
“…One of the reasons has been the limited number of highquality longitudinal studies capturing intersections between predictors of aggression and violent outcomes (Hawkins et al, 2000;Farrington, Gaffney, & Ttofi, 2017). Another factor has been the dearth of European-and UKbased empirical studies over recent decades, with much of the academic literature coming from studies implemented in the United States (Filton, Rongqin, & Fazel, 2018;. Of those, many were influenced by significant scientific advances throughout the twentieth century leading to increasing empirical interest in risk factors associated with relatively fixed personal characteristics such as gender (Messerschmidt, 1993), genetics, and hormones (particularly testosterone) (Carre & Archer, 2018) and personality traits (particularly callous and empathetic traits) (Joliffe & Farrington, 2004).…”
Section: Researching Violencementioning
confidence: 99%
“…Piquero, Jennings, & Barnes, (2012) found 37 studies related to youth violence through analysis of aggregated data found a significant associa-tion between victimization and offending. Two more recent systemic reviews (Filton et al, 2018; exploring the relation-ship between maltreatment and violent offending for instance found relatively few studies in this area. In the former, only 18 high-quality studies were available between 1989 and 2016 (Filton et al, 2018), and in both studies the majority were conducted in the USA (78% & 94%).…”
Section: Violence: the Problemmentioning
confidence: 99%
See 2 more Smart Citations